127k views
4 votes
Solve the following equation for y

Y-3=-5 (x-(-2))

User HelpNeeder
by
5.7k points

2 Answers

3 votes

Answer:

y = -5x -7

Explanation:

So first we distribute the brackets inside: y - 3 = -5 (x + 2)

Then we distribute again: y - 3 = -5x - 10

We are trying to put it in y = mx + b form so we have to isolate y: Add 3 to both sides

y = -5x -7

User Kiford
by
5.2k points
4 votes

Answer:

Y=-5x-7

Steps:

y-3=-5(x-(-2))

y-3=-5(x+2)

y-3=-5x-10

y=-5x-10+3

y=-5x-7

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.